Miscibility in mixtures of liquid crystal 4-[4-(tetradecyloxy)benzoyloxy] benzoic acid and poly(ether imide) - Cakar, Fatih; Ocak, Hale; Bilgin-Eran, Belkis; Ozkal, Selma; Cankurtaran, Ozlem; Karaman, Ferdane (TAYLOR & FRANCIS LTD, 2017)
The miscibility behavior of binary mixtures of polymeric and low molecular weight molecule was studied using viscometric analysis, differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). The miscibility criteria of liquid crystal 4-[4-(tetradecyloxy) benzoyloxy]benzoic acid (TBBA) and poly(ether imide) (Ultem) was investigated at 30 degrees C in dilute chloroform solutions by viscometric analysis. The intrinsic viscosity and viscometric parameters of this mixture system were determined for several TBBA/Ultem mixtures in compositions such as 80/20, 60/40, 40/60 and 20/80 in chloroform solutions. The miscibility criteria on the basis of the sign of ?bm, ?b'm, ?b?m and ?[?]m which are the difference between their experimental and ideal values were calculated by applying equations proposed by Krigbaum-Wall, CatsiffHewett and Garcia et al. The methods were extended to the bulk state by obtaining the criteria from extrapolated experimental data to the zero of reciprocal of concentration. The miscibility of the mixtures was also studied by DSC and FTIR.
Keywords: Liquid crystal; miscibility; poly(ether imide); viscometry; COMPATIBILITY; Chemistry; Crystallography; Materials Science